Perancangan Brand Identity dan Desain Kemasan Aldo Skincare - Nawang Ayu Rahardjo; Novrita Widiyastuti (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2021)
Aldo Skincare is a micro, small and medium enterprise (MSME) that sells serum for the face. However, Aldo Skincare's brand identity and packaging design have not yet formed a brand image and communicated product information, making Aldo Skincare unable to compete with similar local competitors. The brand identity was redesigned using the steps of the work according to Wheeler and the steps of the work of designing the packaging according to Klimchuk and Krasovec. As a result, the key message from Aldo Skincare is “For Healthy, Makes Beauty, Simple for Anyone” while maintaining the identity of the colors previously used. Through this design, a new name was created, namely Aglow by Aldo Baskoro with the tagline "Drop of Wholesome". The design, as a product attribute to convey information and strengthen the brand image, is expected to be able to increase the uniqueness and attractiveness, so that it is indirectly expected to be a means of promotion and become the brand of choice for the audience.